Artystyczna działalność Dmytra Kotki: aspekt wykonawczy oraz stylistyczny - Pater, Anastasja (Musica Galiciana. Kultura muzyczna Galicji w kontekście stosunków polsko-ukraińskich, 2025)
This article undertakes an analysis of the complex and enriched artistic life of conductor Dmytro Kotko, during which his own aesthetic views, organizational skills, manner of working with the choir and creative principles crystallized. The first professional choral ensemble „Ukrainian naddniprianskyi Choir”, headed by D. Kotko, became a kind of creative laboratory where conductor-performative style of the maestro was formed. The conductor's important role in forming professional choral art in the western region of Ukraine is emphasized, and the aspects of conducting and choral work characterized by innovative features are highlighted. Kotko's multifaceted activities acted as a catalyst for the advancement of choral art and, more broadly, musical processes that unfolded in Western Ukraine during the first half of the 20th century.